Analisis Bibliometrik Pemanfaatan Layanan Telemedicine dalam Bidang Obstetri dan Ginekologi: Meta-Analisis - Fatma, Widi; Mahardika Herlambang, Penggalih; Budiyanti, Rani Tiyas (Cermin Dunia Kedokteran, 2026)
Introduction: Telemedicine in health services has various advantages, such as cost flexibility and time efficiency. This research aims to map research related to the application of telemedicine in obstetrics and gynecology. Methods: This study is a quantitative, descriptiveanalytical research using bibliometric analysis of articles published in the Scopus database from 2014 to 2024. Results: We obtained 36 articles on the application of telemedicine in obstetrics and gynecology, with a fluctuating number each year. The country with the most affiliated researchers was the United States, with 19 publications. Most articles were research articles (80.6%) and published in medical journals (67.3%). Conclusion: Based on the study’s results, 4 countries have conducted collaborative research, and 3 keyword mapping clusters relate to the application of telemedicine in obstetrics and gynecology. Cross-sector and cross-border collaboration is necessary, especially in ethical and legal aspects that enable the implementation of cross-border or cross-continental telemedicine. Further research and literature review are needed to assess further the procedures, benefits, and barriers to implementing telemedicine services in obstetrics and gynecology.